Rivers running green: water hyacinth invasion monitored from space. (1st April 2022) - Janssens, Niels; Schreyers, Louise; Biermann, Lauren; van der Ploeg, Martine; Bui, Thanh-Khiet L; van Emmerik, Tim
Abstract: Water hyacinth is an aquatic free-floating plant that is highly invasive, to the extent that it is now present in most freshwater bodies in sub-tropical and tropical regions worldwide. Due to the ecological and socio-economic damages these plants can cause, monitoring their spatial coverage and seasonality is key for development of timely and efficient mitigation measures. Hyacinth patches are sufficiently large to be detectable in high-resolution satellite imagery, allowing for monitoring using freely available remote sensing data collected by platforms such as Sentinel-2. In this study, we estimated water hyacinth coverage and seasonal dynamics over three years (2018–2020) for the Saigon river, Vietnam. Using a Naïve Bayes classifier, hyacinth coverage was mapped in Sentinel-2 imagery with an accuracy of 91%. We show that the dry season (December-May) corresponds to highest water hyacinth abundance, with maximum coverage in February. Lower rainfall and relative humidity were found to be highly correlated ( r = −0.56 and r = −0.64, respectively) with higher hyacinth cover. We also detected substantial interannual variability: annual means in hyacinth coverage varied by a factor of five between the 2018/2019 and 2020 yearly averages, with peak cover occurring in February 2020. The percentage of Saigon river covered by hyacinths over the entire study area peaked at 14% and reached as much as 24% for the upstream section. This confirms the prevalence of these invasive plants in the region, and the growing threat to river navigability and biodiversity. Our study provides an openly available automated workflow for long-term monitoring of hyacinth coverage, which can be scaled-up and extended to other freshwater systems. As such, it provides a step for building a large-scale monitoring tool of this highly invasive species, which may also be used for designing mitigation and reduction strategies of hyacinth and the pollutants it carries along.